Abiotski in biotski odziv na posek in spravilo v primerjavi z neukrepanjem po naravnih ujmah - Rugani, Tihomir (Gozdarski vestnik, 2013)
In our research we analyzed the development of forest stands affected by natural disturbance. We focused on the comparison of vegetation development on salvaged (felling and salvage logging were performed) and non-salvaged (felling and salvage logging were not performed) parts of the damaged forest stands. We measured characteristics of the regeneration on 45 plots in seven study sites in S and W Slovenia. The results indicate differences between the both treatments; under certain conditions, doing nothing after a disturbance can represent a better choice for the development of vegetation and prevention of unfavorable biotic and abiotic processes after a natural disturbance.
Keywords: ujme; ekološka sanacija; gozdovi; fitocenološka analiza; neukrepanje; pomlajevanje